Index of Orthodontic Treatment Need in Referred Nepalese Population - Shrestha, Sujita; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2012)
Objective: The study aims to assess the need for orthodontic treatment in a group of referred Nepalese population of Kathmandu valley. Materials & Method: Dental Health Component (DHC) and Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN) was evaluated on a group of 412 Nepalese orthodontic patients including 142 male and 270 female subjects aged 11-30 years with the mean age 17.12 years by a single examiner. Result: Dental Health Component showed 16 % no/little treatment need, 19.9 % showed borderline need, and 64.1 % showed great/severe treatment need. Aesthetic Component showed 26.5 % no/little treatment need, 32 % showed borderline need, and 41.5 % showed great/severe treatment need. Conclusion: Increasing trend of treatment need for more severe forms of orthodontic problems seen in Nepalese orthodontic patients according to DHC and AC scores in age groups 11-25 years and for both male and female gender groups.